Dampak Ketiadaan Figur Ayah pada Gender Role Development Seorang Anak - Putri, Raissa Dwifandra; Rahmi, Yaumul; Armalid, Ikhwanul Ihsan (Universitas Negeri Malang, 2022)
Abstract: The absence of a father figure is a factor for a child to be involved in social problems, which is like juvenile delinquency. The father plays an important role in the family, namely as a breadwinner, protector, friend, role model, moral guide, teacher, and as an important agent for gender role development of a child. This study aims to examine the impact of the father absence on a child's gender-role development. Research method that used by conducting literature studies related to the research topic, namely the absence of a father figure and the gender role development of a child. Based on the results of a literature review, several impacts were found from the absence of a father figure on a child's gender role development. Nevertheless, other studies also show that there is no difference in the a child's gender role development between children who have a father figure or not. Because most of children who do not have a father figure are found to look for other male figures outside the home as their role models or found their mother as a complete figure for them. Therefore, it is important for parents to be a good role model for their child because this can affect the development of their child, especially in the role of gender role development. Keywords: father absence; gender role; children Abstrak: Ketiadaan figur Ayah menjadi salah satu faktor bagi seorang anak terlibat dalam masalah sosial, salah satunya seperti kenalakan remaja. Ayah memberikan peran penting dalam keluarga, yaitu sebagai pencari nafkah, pelindung, teman, model, penuntun moral, guru, serta merupakan agen penting dalam gender role development seorang anak. Penelitian ini bertujuan untuk mengkaji dampak ketiadaan figur Ayah pada gender-role development seorang anak. Metode penelitian yang digunakan dalam penelitian ini dengan melakukan studi literatur yang berkaitan dengan topik penelitian, yaitu ketiadaan figur ayah dan gender role development seorang anak. Berdasarkan hasil kajian pustaka, didapatkan beberapa dampak dari ketiadaan figur ayah pada gender role development seorang anak. Meskipun demikian, studi – studi lain juga menunjukkan bahwa tidak ada perbedaan perkembangan gender role anak antara anak yang memiliki figur ayah maupun tidak. Sebab anak – anak yang tidak memiliki figur ayah ditemukan bahwa dapat mencari figur laki – laki lain di luar rumah sebagai role modelnya atau melihat ibunya sebagai sosok role model yang diperlukan. Oleh karena itu, penting bagi orang tua untuk dapat menjadi role model bagi seorang anak karena hal ini dapat mempengaruhi perkembangan seorang anak, khususnya dalam perananan gender role developmentnya. Kata kunci: ketiadaan figur ayah; gender role; anak